Cell Membrane Biomimetic Nano-Delivery Systems for Cancer Therapy - Zhenxing Xia; Weiwei Mu; Shijun Yuan; Shunli Fu; Yongjun Liu; Na Zhang (MDPI AG, 2023)
Nano-delivery systems have demonstrated great promise in the therapy of cancer. However, the therapeutic efficacy of conventional nanomedicines is hindered by the clearance of the blood circulation system and the physiological barriers surrounding the tumor. Inspired by the unique capabilities of cells within the body, such as immune evasion, prolonged circulation, and tumor-targeting, there has been a growing interest in developing cell membrane biomimetic nanomedicine delivery systems. Cell membrane modification on nanoparticle surfaces can prolong circulation time, activate tumor-targeting, and ultimately improve the efficacy of cancer treatment. It shows excellent development potential. This review will focus on the advancements in various cell membrane nano-drug delivery systems for cancer therapy and the obstacles encountered during clinical implementation. It is hoped that such discussions will inspire the development of cell membrane biomimetic nanomedical systems.